1992
DOI: 10.1128/jb.174.10.3355-3363.1992
|View full text |Cite
|
Sign up to set email alerts
|

A novel protein, LcrQ, involved in the low-calcium response of Yersinia pseudotuberculosis shows extensive homology to YopH

Abstract: The plasmid-encoded yop genes of pathogenic yersiniae are regulated by the environmental stimuli calcium and temperature. A novel protein, LcrQ, which exhibits a key function in the negative calcium-controlled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
189
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(199 citation statements)
references
References 45 publications
9
189
0
1
Order By: Relevance
“…First the fact that the Y. pseudotuberculosis lcrQ mutant and the Y. enterocolitica yscM1, yscM2 double mutant display a reduction or absence of feedback inhibition when Yop secretion is prevented by Ca 2þ or by a mutation in ysc genes. A second argument would be that overproduction of LcrQ in Y. pseudotuberculosis (Rimpilä inen et al, 1992) and of YscM1 (Allaoui et al, 1995) or YscM2 (this paper) in Y. enterocolitica shuts off Yop synthesis. However, some observations do not fit very well with the regulator hypothesis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…First the fact that the Y. pseudotuberculosis lcrQ mutant and the Y. enterocolitica yscM1, yscM2 double mutant display a reduction or absence of feedback inhibition when Yop secretion is prevented by Ca 2þ or by a mutation in ysc genes. A second argument would be that overproduction of LcrQ in Y. pseudotuberculosis (Rimpilä inen et al, 1992) and of YscM1 (Allaoui et al, 1995) or YscM2 (this paper) in Y. enterocolitica shuts off Yop synthesis. However, some observations do not fit very well with the regulator hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…We also demonstrated that the secretion apparatus is installed and functional even when feedback inhibition is maximal, which is very logical. More importantly, we also addressed the question of the difference in phenotype between the yscM mutant of Y. enterocolitica (Allaoui et al, 1995) and the corresponding lcrQ mutant of Y. pseudotuberculosis (Rimpilä inen et al, 1992). We showed that this difference can be explained by our discovery of yscM2, a second gene functionally identical to yscM1 on the pYV plasmid from Y. enterocolitica.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mutants unable to secrete Yops are downregulated for Yop expression (for reviews see Cornelis, 1992;Forsberg et al, 1994b), whereas a yopN mutant, which hypersecretes Yops, is derepressed for Yop expression . LcrQ is a negative regulatory element that was recently shown to be involved in the feedback regulation of Yop expression (Rimpilä inen et al, 1992;Pettersson et al, 1996). Contact between the pathogen and the eukaryotic cell triggers secretion of LcrQ, which results in increased Yop expression (Pettersson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Shigella and Salmonella systems, the VP-encoded TTS system of Yersinia species contains only one transcriptional activator, VirF (also a member of the AraC family) (Cornelis et al, 1998). Furthermore, in Yersinia species, expression of genes encoding both components of the TTS apparatus and effectors is increased under conditions of active secretion (Lambert de Derouvroit et al, 1992;Rimpilainen et al, 1992). The mechanism by which the TTS apparatus activity is transmitted to VirF has not yet been elucidated, but also involves TTS chaperones (Francis et al, 2001;Wulff-Strobel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%